Legal Perspective on Data Privacy Protection as a Human Right in Indonesia - Palit, Silvester Magnus Loogman; Purba, Tumian Lian Daya (The Easta Journal Law and Human Rights, 2025)
This study examines the legal perspective on data privacy protection as a human right in Indonesia through a normative juridical approach. The increasing use of digital technology and the proliferation of personal data collection have intensified concerns over the misuse of personal information and inadequate legal safeguards. The research analyzes Indonesia’s constitutional provisions, statutory frameworks—including Law No. 27 of 2022 on Personal Data Protection (PDP Law)—and their alignment with international human rights instruments such as the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR). Findings indicate that Indonesia has made substantial progress in establishing a legal foundation for data privacy through the PDP Law, which emphasizes principles of consent, transparency, and accountability. However, implementation challenges remain, particularly in institutional enforcement, public awareness, and regulatory coordination. The study concludes that effective protection of data privacy requires not only strong legal frameworks but also a rights-based approach that upholds human dignity, ensures government accountability, and promotes digital justice in the information age.